Hubungan Motif dan Kepuasan Penggunaan Media Sosial Instagram di Mahasiswa Komunikasi Penyiaran Islam Angkatan 2014-2017 - Sari, Ngudi Ambar; Bukhari, Bukhari; Usman, Usman; Hamzah, Prima Kurinati (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Instagram is one of the most popular social media for the public. One difference between Instagram and other social media, is that instamam is more likely to be used to find information and share information with users than to interact directly with fellow users. The purpose of this study is to find out and explain the motives and active user satisfaction in using Instagram social media and find out the relationship between the motives and satisfaction of Instagram social media usage. This study uses use and gratification theory which assumes that individuals have certain goals in using media. The method used in this research is quantitative research methods. The data collection tool is the questionnaire has been validated. The research sample was 70 people. The sampling technique is simple random sampling. The statistic test that the researchers used was the Partial Correlation Test (Pearson Product Moment). Data is processed using SPSS version 20. The results of this study indicate users want to get information and knowledge that is happening at the present time. Information satisfaction becomes the most obtained by Instagram social media users. Overall Instagram social media has given satisfaction to users and there is a significant relationship between motives and satisfaction.